Decreased serum antioxidant capacity in patients with Wilson disease is associated with neurological symptoms - Bruha, Radan; Vitek, Libor; Marecek, Zdenek; Pospisilova, Lenka; Nevsimalova, Sona; Martasek, Pavel; Petrtyl, Jaromir; Urbanek, Petr; Jiraskova, Alena; Malikova, Ivana; Haluzik, Martin; Ferenci, Peter (Journal of inherited metabolic disease, 2012)
BACKGROUND & AIMS: Wilson disease (WD) is an inherited disorder of copper disposition caused by an ATP7B transporter gene mutation, leading to copper accumulation in predisposed tissues. In addition to a genetic predisposition, other factors are likely to contribute to its clinical manifestation. The aim of the study was to assess whether oxidative stress affects the phenotypic manifestation of WD. METHODS: In 56 patients with WD (29 men; 26 with the hepatic form, 22 with the neurologic form, and eight asymptomatic; mean age 38.5 ± 12 years), total serum antioxidant capacity (TAC) and inflammatory parameters (hs-CRP, IL-1β, IL-2, IL-6, IL-10, and TNF-α) were analyzed and related to the clinical manifestation, and mutations of the ATP7B gene. The control group for the TAC and inflammatory parameters consisted of 50 age- and gender-matched healthy individuals. RESULTS: WD patients had a significantly lower TAC (p < 0.00001), lower IL-10 levels (p = 0.039), as well as both higher IL-1β (p = 0.019) and IL-6 (p = 0.005) levels compared to the control subjects. TNF-α, hs-CRP, and IL-2 did not differ from the controls. Patients with the neurological form of WD had a significantly lower TAC than those with the hepatic form (p < 0.001). In addition, the lower TAC was associated with the severity of the neurological symptoms (p = 0.02). No relationship between the inflammatory parameters and clinical symptoms was found. CONCLUSIONS: Data from our study suggest that the increased oxidative stress contributes significantly to the clinical manifestation of WD; as a lower TAC is associated with the neurological symptoms in WD patients.
Keywords: proteiny přenášející kationty; dospělí; Copper-Transporting ATPases; antioxidancia; Humans; Cation Transport Proteins; Genetic Predisposition to Disease; genetická predispozice k nemoci; lidé středního věku; hepatolentikulární degenerace; Mutation; Middle Aged; Antioxidants; oxidační stres; mužské pohlaví; Hepatolenticular Degeneration; adenosintrifosfatasy; Adult; Nervous System Diseases; Oxidative Stress; Adenosine Triphosphatases; měď; Copper; Interleukin-10; ženské pohlaví; interleukin-6; lidé; nemoci nervového systému; interleukin-10; ATPasy transportující měď; mutace; interleukin-1beta; Male; Interleukin-6; Interleukin-1beta; Female